The High Density Lipoprotein Cholesterol Hypothesis Revisited - Anna Meiliana; Nurrani Mustika Dewi; Andi Wijaya (The Prodia Education and Research Institute (PERI), 2018)
BACKGROUND: The strong inverse association of plasma levels of high-density lipoprotein cholesterol (HDL-C) with coronary heart disease (CHD) found in human epidemiological studies led to the development of the ‘HDL-C hypothesis’, which posits that intervention to raise HDL-C will result in reduced risk of CHD. However, recent evidence has raised doubts about the hypotheses that elevating HDL-C is necessarily therapeutic. Genetic variations that associate with altered HDL-C do not strongly associate with altered cardiovascular disease risk.CONTENT: HDL-mediated cholesterol efflux from macrophage foam cells or measurements of the flux of cholesterol from macrophages to the liver and feces seem to correlate better with atherosclerotic burden than with HDL-C levels. Thus, it may be time to modify the HDL-C hypothesis to the ‘HDL flux hypothesis’, where intervention to promote cholesterol efflux and reverse cholesterol transport will reduce CHD risk, regardless of whether it affects plasma HDL-C levels. A deeper understanding of the complex biology of HDL metabolism and its relationship to reverse cholesterol transport and atherothrombotic events is urgently needed. This might lead to biomarkers of HDL flux and functionality that are more informative than simple measurements of HDL-C levels.SUMMARY: It is now clear from recent clinical trial and genetic studies that some approaches to raising HDL-C levels may have no effect on CHD. This suggests the need to evaluate HDL-C-raising therapies in different clinical populations, as well as therapies targeted toward HDL flux and function rather than simply HDL-C elevation. Perhaps moving from a focus on the HDL-C hypothesis to a focus on the HDL flux hypothesis will permit a biologically based reassessment of the optimal therapeutic approach to targeting HDL for reduction in cardiovascular risk.KEYWORDS: reverse cholesterol transport, cholesterol efflux capacity, HDL dysfunction, HDL particle size, HDL lipidomics, HDL proteomics